2021
DOI: 10.15361/2175-0106.2021v37n4p254-257
|View full text |Cite
|
Sign up to set email alerts
|

Uso Da Hidrodissecção Para Remoção De Flap Conjuntival Em 360° Em Cão – Relato De Caso

Abstract: O objetivo desse trabalho foi relatar um caso onde foi usado a hidrodissecção para auxiliar na remoção da aderência de flap conjuntival em 360° em córnea, em um cão. Foi atendido um cão da raça buldogue francês, macho, 2 anos, 18 kg, apresentando olho esquerdo com presença de um flap conjuntival em 360°, em decorrência de tratamento prévio de uma úlcera em melting extensa há 40 dias. Após a realização de exames pré-operatórios de rotina, o paciente foi submetido a um novo procedimento cirúrgico para remoção do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Hydrodissection has been described for the first time in the construction of conjunctival flaps in normal dogs, and the authors concluded that it is an easy procedure that optimizes the creation of conjunctival flaps, thus becoming a new option for surgeons, especially for beginning ophthalmologists [ 21 ]. However, we believe that it is important to continue studies of conjunctival flap construction in routine clinical situations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hydrodissection has been described for the first time in the construction of conjunctival flaps in normal dogs, and the authors concluded that it is an easy procedure that optimizes the creation of conjunctival flaps, thus becoming a new option for surgeons, especially for beginning ophthalmologists [ 21 ]. However, we believe that it is important to continue studies of conjunctival flap construction in routine clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Longer operative time significantly contributes to the risk of complications, particularly infection [ 27 ]. The operative time spent in the construction of conjunctival flaps in normal dogs was analyzed, and no change was observed [ 21 ]. Several factors, such as pre-operative planning, surgeon experience, and fatigue, may prolong the operative duration [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations